Management and organization of farms - Ergashev Mukhammadali Sobirjon ugli; Tojiddinov Sardorbek Abduvahob ugli (Genius Publishing Group, 2022)
This article discusses farm management and how to manage it properly. All information in the article is the personal opinion of the author and is derived from the practical processes in the learning process
Keywords: Farm; Management; Condition